Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: \(P=\left(\dfrac{3}{2\left(x+2\right)}-\dfrac{x}{x-2}+\dfrac{2x^2+3}{\left(x-2\right)\left(x+2\right)}\right)\cdot\dfrac{4\left(x-2\right)}{2x-1}\)
\(=\left(\dfrac{3\left(x-2\right)}{2\left(x+2\right)\left(x-2\right)}-\dfrac{2x\left(x+2\right)}{2\left(x-2\right)\left(x+2\right)}+\dfrac{4x^2+6}{2\left(x-2\right)\left(x+2\right)}\right)\cdot\dfrac{4\left(x-2\right)}{2x-1}\)
\(=\dfrac{3x-6-2x^2-4x+4x^2+6}{2\left(x+2\right)\left(x-2\right)}\cdot\dfrac{4\left(x-2\right)}{2x-1}\)
\(=\dfrac{2x^2-x}{x+2}\cdot\dfrac{2}{2x-1}=\dfrac{2x}{x+2}\)
b: Khi 4x2-1=0 thì (2x-1)(2x+1)=0
=>x=1/2(loại) và x=-1/2(nhận)
Khi x=-1/2 thì \(P=\left(2\cdot\dfrac{-1}{2}\right):\left(-\dfrac{1}{2}+2\right)=-1:\dfrac{3}{2}=-\dfrac{2}{3}\)
Với `x \ne +-2,x \ne 1/2,x \ne0`. Ta có:
`(3/[2x+4]+x/[2-x]+[2x^2+3]/[x^2-4]):[2x-1]/[4x-8]`
`=(3/[2(x+2)]-x/[x-2]+[2x^2+3]/[(x-2)(x+2)]).[4(x-2)]/[2x-1]`
`=[3(x-2)-2x(x+2)+2(2x^2+3)]/[x(x-2)(x+2)].[4(x-2)]/[2x-1]`
`=[3x-6-2x^2-4x+4x^2+6]/[x(x+2)]. 4/[2x-1]`
`=[2x^2-x]/[x(x+2)]. 4/[2x-1]`
`=[x(2x-1)]/[x(x+2)] . 4/[2x-1]`
`=4/[x+2]`
Answer:
\(\left(2x+1\right)^2+\left(2x-1\right)^2-2\left(1+2x\right)\left(2x-1\right)\)
\(=(4x^2+4x+1)+(4x^2-4x+1)-2(4x^2-1)\)
\(=4x^2+4x+1+4x^2-4x+1-8x^2+2\)
\(=(4x^2+4x^2-8x^2)+(4x-4x)+(1+1+2)\)
\(=4\)
\((x-1)^3-(x+2)(x^2-2x+4)+3(x-1)(x+1)\)
\(=(x^3-3x^2+3x-1)-(x^3+8)+3(x^2-1)\)
\(=x^3-3x^2+3x-1-x^3-8+3x^2-3\)
\(=(x^3-x^3)+(-3x^2+3x^2)+3x+(-1-8-3)\)
\(=3x-12\)
1:
a: \(\left(2x-5\right)^2-4x\left(x+3\right)\)
\(=4x^2-20x+25-4x^2-12x\)
=-32x+25
b: \(\left(x-2\right)^3-6\left(x+4\right)\left(x-4\right)-\left(x-2\right)\left(x^2+2x+4\right)\)
\(=x^3-6x^2+12x-8-\left(x^3-8\right)-6\left(x^2-16\right)\)
\(=-6x^2+12x-6x^2+96=-12x^2+12x+96\)
c: \(\left(x-1\right)^2-2\left(x-1\right)\left(x+2\right)+\left(x+2\right)^2+5\left(2x-3\right)\)
\(=\left(x-1-x-2\right)^2+5\left(2x-3\right)\)
\(=\left(-3\right)^2+5\left(2x-3\right)\)
\(=9+10x-15=10x-6\)
2:
a: \(\left(2-3x\right)^2-5x\left(x-4\right)+4\left(x-1\right)\)
\(=9x^2-12x+4-5x^2+20x+4x-4\)
\(=4x^2+12x\)
b: \(\left(3-x\right)\left(x^2+3x+9\right)+\left(x-3\right)^3\)
\(=27-x^3+x^3-9x^2+27x-27\)
\(=-9x^2+27x\)
c: \(\left(x-4\right)^2\left(x+4\right)-\left(x-4\right)\left(x+4\right)^2+3\left(x^2-16\right)\)
\(=\left(x-4\right)\left(x+4\right)\left(x-4-x-4\right)+3\left(x^2-16\right)\)
\(=\left(x^2-16\right)\left(-8\right)+3\left(x^2-16\right)\)
\(=-5\left(x^2-16\right)=-5x^2+80\)
b/ \(4\left(x-1\right)\left(x+1\right)-5x\left(x-2\right)+x^2\)
= \(4\left(x^2-1\right)-5x^2+10x+x^2\)
= \(4x^2-4-5x^2+10x+x^2\)
= \(10x-4\)
= \(2\left(5x-2\right)\)
c/ \(\left(3-2x\right)\left(x-2\right)+4\left(x-1\right)\left(x-3\right)-2\left(x-2\right)\left(x+2\right)\)
= \(3x-6-2x^2+4x+4\left(x^2-4x-4\right)-2\left(x^2-4\right)\)
= \(3x-6-2x^2+4x+4x^2-16x-16-8x^2-18\)
= \(-9x-12\)
= \(-3\left(3x+4\right)\)
a) \(\left(x-1\right)^2-\left(x+3\right)^2+\left(x+4\right)\left(x-4\right)\)
\(=x^2-2x+1-\left(x^2+6x+9\right)+x^2-16\)
\(=x^2-2x+1-x^2-6x-9+x^2-16=-8x-24\)
b)
\(2\left(3x-2\right)^2-3\left(2x+5\right)^2-6\left(x+1\right)\left(x-1\right)\)
\(=2\left(9x^2-12x+4\right)-3\left(4x^2+20x+25\right)-6\left(x^2-1\right)\)
\(=18x^2-24x+8-12x^2-60x-75-6x^2+6=-84x-61\)